Bank Bailouts and Fiscal Contingent Liabilities - Mare, Davide S. (The World Bank, 2023)
Implicit government guarantees to bail out troubled banks can produce a sizable fiscal contingent liability. Drawing on a rich history of various forms of staggered bailouts, this paper studies the link between bank bailouts and fiscal contingent liabilities using bank-level data for Kazakhstan-an upper-middle-income country in Central Asia. The paper first estimates the probability that a bank in distress is bailed out, conditioning on bank characteristics and financial soundness. Second, it estimates the magnitude of bailout costs depending on the size of banks, their ownership type, financial soundness, and the type of bailout instrument used by the government. The latter aims to contrast the fiscal contingent liabilities when the government uses bailout instruments without recourse on bank future profits-such as government purchases of bad loans at 100 percent nominal value-versus instruments that do not allow bank owners to socialize losses and privatize gains-such as properly governed and priced senior debt or equity injections. Third, the paper illustrates how the estimations could be used for projecting the expected contingent liabilities from bank bailouts
Keywords: Bank Bailout; Bank Distress; Banking Law; Bankruptcy and Resolution of Financial Distress; Contingent Liabilities; Finance and Financial Sector Development; Fiscal Cost; Law and Development; Problem Bank Resolution; Socialize Bank Loss; Systemic Importance